2007
DOI: 10.1161/circulationaha.106.675041
|View full text |Cite
|
Sign up to set email alerts
|

Superior Cardiovascular Effect of Aerobic Interval Training Versus Moderate Continuous Training in Heart Failure Patients

Abstract: Background-Exercise training reduces the symptoms of chronic heart failure. Which exercise intensity yields maximal beneficial adaptations is controversial. Furthermore, the incidence of chronic heart failure increases with advanced age; it has been reported that 88% and 49% of patients with a first diagnosis of chronic heart failure are Ͼ65 and Ͼ80 years old, respectively. Despite this, most previous studies have excluded patients with an age Ͼ70 years. Our objective was to compare training programs with mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

92
1,685
25
75

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,697 publications
(1,943 citation statements)
references
References 40 publications
92
1,685
25
75
Order By: Relevance
“…In smaller studies, HIIT protocols have a clear benefit to MICT protocols. 3,32,60 In all three studies, O2 uptake/aerobic capacity was significantly higher in the HIIT participant subgroups. Additionally Wisløff and colleagues found that HIIT was…”
Section: Role Of Exercise Intensitymentioning
confidence: 74%
See 2 more Smart Citations
“…In smaller studies, HIIT protocols have a clear benefit to MICT protocols. 3,32,60 In all three studies, O2 uptake/aerobic capacity was significantly higher in the HIIT participant subgroups. Additionally Wisløff and colleagues found that HIIT was…”
Section: Role Of Exercise Intensitymentioning
confidence: 74%
“…However, more recent studies by Wisløff and others have shown that ET can elicit beneficial peripheral metabolic adaptations in patients with HF, resulting in a paradigm shift in favor of structured ET as an integral component of CR. 3,21 Despite favorable data and Class I recommendations, most eligible CHD patients do not enroll in CR. Likely reasons are that referrals for these programs are often not part of routine care for many physicians and access to facilities is difficult in rural areas.…”
Section: Indications Contraindications and Cr Utilizationmentioning
confidence: 99%
See 1 more Smart Citation
“…A Swedish study showed a 31% reduced risk for incident MI associated with high versus low leisure‐time physical activities 34. Earlier studies with data on high‐ and moderate‐intensity exercise among CVD patients found that both intensity levels decreased CVD risk, but also pointed to the knowledge gap regarding the right intensity and amount of physical activity in secondary prevention of CVD 35, 36, 37…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the continuous training protocol, the higher intensity interval training regimen induced superior responses for a number of whole body and muscle measures, including insulin sensitivity (determined from the HOMA index), : V O 2max , skeletal muscle markers of mitochondrial biogenesis and insulin signalling, as well as endothelial function. This same group has also reported that intense interval training is superior to continuous moderate intensity training for inducing specific health-related benefits in obese individuals [33] and patients with heart failure [34], and the general conclusion given by the authors is that high-intensity exercise training programmes may yield more favourable results than programmes employing low-to moderate-intensity exercise.…”
Section: The Study's Findingsmentioning
confidence: 90%